Isokinetic muscle function, dynamic balance, and injury risk in dominant and non-dominant lower extremities of adolescent taekwondo athletes - Dong, Mingyuan; Kim, Boseoung; Lee, Jiyoung; Choi, Yongchul; Shi, Panpan; Zhang, Guanmin (Frontiers in Sports and Active Living, 2025)
BackgroundAdolescent Taekwondo athletes are exposed to distinct musculoskeletal demands, where imbalances in muscle function and deficiencies in dynamic balance may increase their risk of injury.ObjectiveThis study aimed to assess the effects of Taekwondo training on isokinetic muscle function, dynamic balance, and injury risk in dominant and non-dominant lower limbs of adolescent athletes.MethodsForty adolescent Taekwondo athletes (n = 40; 27 males, 13 females; mean age: 16.07 years) with an average of 7.07 years of training experience participated in this study. Participants underwent isokinetic muscle function tests (60°/s and 180°/s) and the Y-Balance Test (YBT) on both dominant and non-dominant lower limbs to assess muscular strength and dynamic balance. Physical characteristics including height, weight, and body fat percentage were also recorded.ResultsSignificant differences in knee extensor strength were observed between dominant and non-dominant limbs at 60°/s (p < 0.05), whereas flexor strength did not differ significantly. At 180°/s, significant asymmetries were found in ankle dorsiflexor strength and ipsilateral balance ratios between dominant and non-dominant sides. YBT composite scores were below the 85% threshold in several athletes, indicating an elevated injury risk. Correlation analysis showed strong associations between lower limb asymmetries and injury occurrences, especially among athletes with right-side dominance.ConclusionThese findings emphasize the critical need for bilateral neuromuscular training protocols to mitigate injury risks in adolescent Taekwondo athletes, highlighting the presence of muscle imbalances and reduced dynamic balance in this population.